2020
DOI: 10.1002/dc.24559
|View full text |Cite
|
Sign up to set email alerts
|

The continuing role of breast fine‐needle aspiration biopsy after the introduction of the IAC Yokohama System For Reporting Breast Fine Needle Aspiration Biopsy Cytopathology

Abstract: Background: Ultrasound-guided fine-needle aspiration biopsy (FNAB) (US-guided FNAB) is a rapid and cost-effective procedure for the diagnosis of breast lesions. Our Institution has a long tradition in breast FNAB performed by cytopathologists; recently we adopted both US guidance and a five-tiered classification system similar to that proposed by the International Academy of Cytology (IAC). The aim of this study was to demonstrate the continuing role of US-guided FNAB in the diagnosis of breast lesions, despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 37 publications
8
30
1
1
Order By: Relevance
“…Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…A comprehensive literature search through PubMed database identified a total of seven studies implementing IAC Yokohama reporting system for breast FNAB. [6][7][8][9][10][11][12] A comparison of the test performance across these studies was highlighted in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…When a diagnosis of low‐grade ductal in situ carcinoma is made (in the atypical or suspicious categories), a biopsy may be necessary. However, a recent series from an Italian reference centre has shown that, when performed by experienced cytopathologists following the Yokohama system, the majority of diagnoses are either benign or malignant 31 …”
Section: Fine Needle Aspiration Biopsies Of the Breastmentioning
confidence: 99%